Computer-based solar tracking system for PV energy yield improvement - Rini Nur Hasanah; Aditya Bagus Setyawan; Eka Maulana; Tri Nurwati; Taufik Taufik (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Electric energy is the main driver of various daily activities, both to increase productivity as well as to improve life quality. Energy demand is continuously increasing in parallel to the progress in technology and population growth. Depletion of fossil energy sources and awareness of environmental protection make people resort to renewable energy sources like solar energy. Low efficiency and intermittent characteristic of solar energy may originate from the sun movement along the day as well as the year. Efforts have always been tried to deal with the drawbacks. This paper proposes a computer-based tracking system to fully monitor and control a solar panel movement. The designed system has proven a good performance of working at certain time intervals, either hourly, or even continuously, as desired. Energy yield improvement has been achieved by processing the tracking results with the help of a microcontroller to optimize the power generation of the solar panel.